Evaluating the Route of Antibiotic Administration and its Effect on Nursery Pig Growth Performance - W. M. Hutchens; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband; H. I. Calderón; K. Habib; V. Ishengoma; T. G. Nagaraja; R. G. Amachawadi (Kansas Agricultural Experiment Station Research Reports, 2020)
This experiment was conducted to determine the influence of the route of antibiotic administration (in-feed vs. in-water) on nursery pig growth performance. A total of 2,592 pigs (L337 × 1050, PIC Hendersonville, TN; initially 14.5 lb) were used in a 28-d trial. Pigs were weaned at 21 d of age and placed in a commercial research facility with 27 pigs per pen. After a 7-d pre-trial period, pens of pigs were assigned to weight blocks in a randomized complete block design. There were 12 replications per treatment with pen as experimental unit for in-feed medication treatments and a pair of pens as the experimental unit for water medication treatments. The six treatments included a control (no medication), chlortetracycline (CTC) provided via feed or water to achieve 9.98 mg/lb body weight (BW), tiamulin in feed (2.27 mg/lb BW) or water (10.43 mg/lb BW), or a combination of CTC and tiamulin in feed. Experimental treatments were provided for 14-d followed by a 14-d period without medication. For statistical analysis, the interaction of antibiotic type × route of administration was tested in a 2 × 2 factorial with main effect of antibiotic type (CTC or tiamulin) and route of administration (in-feed or in-water). Pairwise comparisons were also made between the control and all individual treatments. From d 0 to 14 (P<0.05), d 14 to 28 (P<0.10), and d 0 to 28 (P<0.05) there was an antibiotic × route of administration interaction observed for average daily gain (ADG). The interactions were a result of pigs fed diets containing CTC having improved (P<0.05) ADG compared to CTC in-water, whereas pigs provided tiamulin in-water exhibited improved ADG compared with tiamulin in feed. There was an antibiotic × route of administration interaction observed for feed-to-gain ratio (F/G) from d 0 to 14 and 0 to 28. Pigs provided tiamulin in the feed had the poorest F/G, whereas F/G was not different among the other treatments. Providing CTC in the feed or water or tiamulin in the water improved (P<0.05) ADG compared to pigs fed the control diet. Providing either CTC or tiamulin in the feed increased (P<0.05) average daily feed intake (ADFI) as compared with providing the antibiotics in water. Pigs fed antibiotics in the feed had increased (P<0.05) ADFI compared to the control with those provided antibiotics in the water being marginally greater (P<0.10) in ADFI than the control. For ADG (d 0 to 28), pigs provided CTC in feed, tiamulin in the water, or the combination of CTC and tiamulin in the feed during the treatment period had increased ADG (P<0.05) compared to pigs fed the control diet. For ADFI, there was no evidence of an interaction or main effects; however, when compared to the control, pigs provided CTC in-feed, tiamulin in-water, or the combination in the feed all had increased ADFI. In summary, providing CTC in feed with or without tiamulin or tiamulin in the water improved nursery pig growth performance.
Keywords: antibiotics; administration; nursery; pigs